Oligopsony, Institutions and the Efficiency of General Training - Gylfi Zoega; Marco Francesconi; Alison L. Booth (Institute for the Study of Labor (IZA), 2002)
In oligopsonistic labour markets, firms have some market power, and a wedge is created between wages and marginal product. When oligopsonistic firms' production technology requires generally trained workers, firms may therefore receive part of the returns to general training and be willing to pay for it despite its general nature. However this outcome is not efficient, in the sense that too few workers are trained and workers who are hired receive too little training. We consider how different institutions can affect this inefficiency. Industry-level minimum wages can remove the training inefficiency and provide workers with the right incentives to invest in general training. A training subsidy to firms can also be used to achieve first-best. Trade unions might also remedy the market failure, in two ways. First, if an industry-wide union has a direct say in the training decision and maximises the utility of a representative worker, it will choose the efficient level of training intensity. Second, firmspecific unions, through raising relative wages and reducing turnover, can increase training intensity.
Keywords: E32; J23; J24; J54; 330; training; oligopsony; unions; minimum wages; Betriebliche Bildungsarbeit; Lohn; Arbeitsmarkt; Arbeitsnachfrage; Oligopol; Marktmacht; Mindestlohn; Berufsbildungspolitik; Gewerkschaftliche Gewerkschaftlicher Organisationsgrad; Theorie